Тусгай хамгаалалттай газрын менежментийн өнөөгийн байдал хэтийн төлөв - Эрдэнэчимэг, Н (Proceedings of the Mongolian Academy of Sciences, 2016)
The paper discusses the stages of development of the protected areas network in Mongolia. Urban sprawl is affecting Bogd-Ula SPA as its northern edges have been absorbed by urban expansion (primarily high-end apartment buildings) of the capital Ulaanbaatar.